2013
DOI: 10.1007/s10029-013-1061-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of antibiotic prophylaxis in elective inguinal hernia repair in adults in London and south-east England: a cross-sectional survey

Abstract: PurposeEvidence regarding whether or not antibiotic prophylaxis is beneficial in preventing post-operative surgical site infection in adult inguinal hernia repair is conflicting. A recent Cochrane review based on 17 randomised trials did not reach a conclusion on this subject. This study aimed to describe the current practice and determine whether clinical equipoise is prevalent.MethodsSurgeons in training were recruited to administer the Survey of Hernia Antibiotic Prophylaxis usE survey to consultant-level g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…73% of the clean procedures audited received antibiotics incorrectly and the questionnaire further depicted the general attitude that procedures such as inguinal hernia repair should receive antibiotics. This practice is similar to other studies where surgeons give AP in clean surgery [22,23]. There is ambiguity in the literature with some papers advocating antibiotics in clean procedures [24,25] and others not [26,27].…”
Section: Discussionsupporting
confidence: 57%
“…73% of the clean procedures audited received antibiotics incorrectly and the questionnaire further depicted the general attitude that procedures such as inguinal hernia repair should receive antibiotics. This practice is similar to other studies where surgeons give AP in clean surgery [22,23]. There is ambiguity in the literature with some papers advocating antibiotics in clean procedures [24,25] and others not [26,27].…”
Section: Discussionsupporting
confidence: 57%
“…Despite this, prophylactic antibiotics were administered to 18 % of patients in this study. This is surprising given SIGN guidance, but not entirely out of keeping with practises in other parts of the UK, as a recent survey of 229 surgeons in the South East of England has shown that 79 % of hospital guidelines and 84 % of surgeons supported the use of antibiotic prophylaxis in inguinal hernia surgery [18]. The overall use of prophylactic antibiotics in inguinal hernia surgery in Scotland has reduced from its previous level of 71 % in 1998/9 so it appears that SIGN guidance has made an impact [11].…”
Section: Discussionmentioning
confidence: 84%
“…those without risk factors for SSI). They justify their approach by the presence of an implant, despite the lack of sufficient clinical evidence to support this course of action [21]. …”
Section: Antibiotic Prophylaxis In Hernia Repair Proceduresmentioning
confidence: 99%
“…They base this opinion on their own beliefs and experience. Furthermore, 22 out of 28 hospitals interrogated in this region include antibiotic prophylaxis in their guidelines [21]. …”
Section: Introductionmentioning
confidence: 99%